Productivity, Welfare and Reallocation : Theory and Firm-Level Evidence - Basu, Susanto; Pascali, Luigi; Schiantarelli, Fabio; Serven, Luis (2012)
A considerable literature has focused on the determinants of total factor productivity (TFP), prompted by the empirical finding that TFP accounts for the bulk of long-term growth. This paper offers a deeper reason for such focus: the welfare of a representative consumer is summarized by current and anticipated future Solow productivity residuals. The equivalence holds for any specification of technology and market structure, as long as the representative household maximizes utility while taking prices parametrically. This result justifies total factor productivity as the right summary measure of welfare, even in situations where it does not properly measure technology, and makes it possible to calculate the contributions of disaggregated units (industries or firms) to aggregate welfare using readily available data. Based on this finding, the authors compute firm and industry contributions to welfare for a set of European countries (Belgium, France, Great Britain, Italy, Spain) using industry-level and firm-level data. With additional assumptions about technology and market structure (specifically, that firms minimize costs and face common factor prices), the authors show that welfare change can be further decomposed into three components that reflect, respectively, technical change, aggregate distortions, and allocative efficiency. Then, using the appropriate firm-level data, they assess the importance of each of these components as sources of welfare improvement in the same set of European countries.